2005
DOI: 10.1007/s00436-005-1400-0
|View full text |Cite
|
Sign up to set email alerts
|

Causes of inter-individual variation in reproductive strategies of the parasitic nematode Graphidioides subterraneus

Abstract: Several factors capable of affecting the amount of resources available to an individual parasite, such as the number of other parasites in the host or host quality, may cause variability in reproductive success among parasites. Variation in egg output and mean egg volume was investigated among adult females of the nematode Graphidioides subterraneus, parasitic in the herbivorous subterranean rodent Ctenomys talarum (Octodontidae). Female nematode body size correlated strongly with the number of eggs produced. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 24 publications
1
17
0
2
Order By: Relevance
“…Concerning clutch size variation in laying females we found that the number of laid eggs was partly explained by body size (females with larger thorax and wider abdomen laid more eggs), as expected from the generally accepted relationship between body size and fecundity (Fox and Czesak 2000;Branquart and Hemptinne 2000;Rossin et al 2005). However, we also found a negative relationship between abdomen length and number of laid eggs.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Concerning clutch size variation in laying females we found that the number of laid eggs was partly explained by body size (females with larger thorax and wider abdomen laid more eggs), as expected from the generally accepted relationship between body size and fecundity (Fox and Czesak 2000;Branquart and Hemptinne 2000;Rossin et al 2005). However, we also found a negative relationship between abdomen length and number of laid eggs.…”
Section: Discussionsupporting
confidence: 62%
“…The aims of our study are: (1) to provide basic information on the reproductive anatomy and fecundity of C. hemapterus, (2) to assess the validity of an experimental method to estimate fecundity in this species, (3) to explore whether the general relationship between body size and fecundity (Fox and Czesak 2000;Branquart and Hemptinne 2000;Rossin et al 2005) is applicable in C. hemapterus.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a myriad of factors affect the reproductive resources available to individual parasites, such as host suitability, host diet and intra-and inter-specific competition (Boddington & Mettrick, 1981;Holland, 1984;Dobson, 1986;Crompton et al, 1988;Shostak & Scott, 1993;Marcogliese, 1997). Parental quality may be translated into variation in egg size or quantity, traits known to vary intraspecifically in parasites (Rossin et al, 2005;Herreras et al, 2007). Fine-tuned, adaptive parental effects can evolve when the adult environment gives cues about the environment of larval parasites.…”
Section: Introductionmentioning
confidence: 99%
“…A phenotypic tradeoff between propagule number and propagule size within a given population is considered to occur when these two traits are negatively correlated but very often this pattern is not observed in nature (Roff 1992, 2002, Stearns 1992, Bernardo 1996. Indeed, it has not been found in the two parasite populations studied to date (Rossin et al 2005, Timi et al 2005, but note that failure to reveal phenotypic tradeoffs does not necessarily ensure their absence. In a seminal paper, van Noordwijk and de Jong (1986) developed a model to illustrate how individual differences in acquisition and allocation of resources can explain why underlying tradeoffs may go unnoticed.…”
mentioning
confidence: 99%